PENGARUH KESESUAIAN TUGAS, PELATIHAN DAN EFEKTIVITAS PENERAPAN SISTEM INFORMASI AKUNTANSI TERHADAP KINERJA KARYAWAN PADA LEMBAGA PERKREDITAN DESA (LPD) PEMAKAI SISTEM DIGITAL DI KABUPATEN BADUNG - Ni Putu Dila Ristya Rahayu; Komang Fridagustina Adnantara; Laras Oktaviani (Universitas Triatma Mulya, 2022)
The application of information technology is an important thing to do because information technology has a strategic role for the governance and development of a business entity, including LPD especially in the financial sector. LPD management in badung regency is inseparable from the use of information technology. This information technology is used to manage online transactions, such as paying electricity bills and making financial reports. This study aims to determine the effect of task suitability, training and the effectiveness of the application of accounting information systems on employee performance. The population in this study is the Lembaga Perkreditan Desa (LPD) in Badung Regency with the sample used as many as 168 respondents. The data analysis technique used in this research is multiple linear regression. Based on the results of the study, it can be seen that : (1) the suitability of the accounting information system task has a positive and significant effect on employee performanc. (2) accounting information system training has a significant positive effect on employee performance. (3) the effectiveness of the application of accounting information systems has a significant and positive effect on employee performance. The magnitude of the influence of independent variables on employee performance is 50.7%, while the remaining 49,3% is influenced by other factors outside of this study.